Is there life after Buckley’s Formocresol? Part I – A narrative review of alternative interventions and materials - V. SRINIVASAN, C. L. PATCHETT, & P. J. WATERHOUSE (Paediatric Dentistry, 2006)
The disquiet among the dental profession over the use of formocresol in the management of primary teeth has led in the past to the evaluation of possible alternatives to the medication.